(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The fact shows that science learning in Class VIII at SMP Negeri 8 Gorontalo has a problem, namely the low learning outcomes of students, this is caused by the lack of interest of students in learning science. Learning is more centered on the teacher. Students take more notes and memorize the material in the textbook. The method used is less attractive to students. Lack of use of media in learning. The teacher lacks apperception that can provoke students to ask questions, this causes boredom in students because students are only directed to the ability to memorize and write material which results in activities and learning outcomes of students not achieving completeness, while what is expected in science learning in elementary schools so that students are able to know and understand the various organs of the body and diseases in humans. In addition, teaching science in elementary schools aims to foster students’ understanding of human relations with life and understand the condition of the universe around them, so that they are able to adapt to the environment according to their age level, circumstances and abilities. However, the problem that occurs in the implementation of education is the low quality of education which results in student learning outcomes below the KKM .